EFFET BACTÉRICIDE ET ÉPURATOIRE DE TRAITEMENT ÉLECTROCHIMIQUE SUR L’EFFLUENT D’ABATTOIR DE VIANDE ROUGE - Abdelaziz, Khennoussi; Nour-eddine, Ameziane; Abdelkader, Chahlaoui; Mehdi, Chaouch (European Scientific Journal, ESJ, 2013)
Effluent from red meat slaughter are characterized by a significant microbiological and organic load; coliform indicators of faecal contamination, pathogenic bacteria, and parasites. The spread of pathogens from the effluent and sludge resulting from their treatment, are a potential microbiological risk to the receiving environment and public health. Treatment by electrocoagulation with iron electrodes and aluminum allows a reduction of 5 logarithmic units of coliforms, the elimination of bacteria up to 100% (total disinfection) with the increase of the voltage and the addition of sodium chloride.